Portugal - Simões, Teresa (2013)
Portugal has its most valuable energy asset in renewable energy resources. It is one of the countries of Europe with a high level of sun radiation, considerable vegetable and animal biomass potential, and a good wind resource. Portugal also has available hydro resources and possibilities for ocean energy (when that technology reaches maturity). Although Portugal still depends largely on foreign countries for oil, gas, and coal, especially for the transportation sector, in recent years the country has taken a clear path towards a sustainable, renewable-based, electricity generation. The energy contribution and the investments in the renewable energies are becoming more relevant every year as a strategically sector for the development of the country’s economy. By the end of 2007, Portugal had installed 7,409 MW (1) of renewable-based power plants. That capacity has generated an estimated 18, 207 GWh (2) during 2007. Renewable sources have contributed an estimated 36.4% of the total electricity demand, one of the highest percentages in Europe. The goals defined for 2010 and 2013 of 39% and 45% of the national electricity demand generated from RES, respectively are within reach. In 2007, fewer wind parks were installed than in previous years. However, the second phase of the public call for grid connection of wind power capacity, started in 2005 was concluded in August 2007. As a result, 400 MW were added to the 1,200 MW attributed in 2006. It is expected that wind energy capacity growth will increase again in the next few years.